2020
DOI: 10.1001/jamanetworkopen.2020.6646
|View full text |Cite
|
Sign up to set email alerts
|

Association of Specific Mental Disorders With Premature Mortality in the Danish Population Using Alternative Measurement Methods

Abstract: IMPORTANCE The association of mental disorders with premature mortality published in the Global Burden of Disease (GBD) studies has been underestimated because these analyses have recommended using only a small number of mental disorders as causes of death to estimate years of life lost (YLL). Alternative methods have been introduced, such as estimating life-years lost (LYL), to compare individuals with mental disorders with the general population. OBJECTIVES To generate register-based YLL and LYL estimates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 29 publications
(33 reference statements)
2
66
0
Order By: Relevance
“…Data suggest that the same people who experience psychiatric conditions when they are young experience age-associated physical diseases when they are older. 3 , 4 Excess risk of physical disease and mortality among individuals with mental disorders has been detected in data from community surveys and outpatient and inpatient hospital records 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 and in data across different countries 4 , 13 , 14 , 15 , 16 and socioeconomic strata. 17 , 18 These findings suggest that preventing mental disorders in youth might be associated with the prevention of physical diseases and disabilities in older adulthood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data suggest that the same people who experience psychiatric conditions when they are young experience age-associated physical diseases when they are older. 3 , 4 Excess risk of physical disease and mortality among individuals with mental disorders has been detected in data from community surveys and outpatient and inpatient hospital records 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 and in data across different countries 4 , 13 , 14 , 15 , 16 and socioeconomic strata. 17 , 18 These findings suggest that preventing mental disorders in youth might be associated with the prevention of physical diseases and disabilities in older adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies have used end-of-life measures of poor physical health, such as all-cause mortality, cause of death, or years of life lost. 7 , 10 , 13 , 14 , 15 , 16 , 20 Estimates of earlier outcomes (such as onset of first physical disease or number of disease episodes) would inform prevention efforts. Furthermore, studies estimating associations between mental disorders and physical diseases have largely relied on cross-sectional designs or follow-up periods of less than 15 years, with longer follow-up reserved for studies of mortality outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the types of mental disorders included in the Global Burden of Disease study, we have recently demonstrated that those with two or more types of mental disorders have a shorter life expectancy (i.e., more life‐years lost) compared to those with one type of mental disorder 12 . There is a need to more precisely map the associations between specific combinations of mental disorders and excess mortality.…”
mentioning
confidence: 99%
“…Based on our previous observations that common disorders such as mood disorders, neurotic/stress‐related/somatoform disorders and substance use disorders were each associated with appreciable risks of developing a range of other disorders 2 , we predicted that these disorders would be found in many common combinations. Furthermore, since we estimated that substance use disorders were strongly associated with premature mortality (when looking both at mortality rates and life expectancy) 7 , and that life expectancy was shorter for those with two or more types of mental disorders 12 , we predicted that combinations including substance use disorders or a larger number of disorders would be associated with greater risk of premature mortality.…”
mentioning
confidence: 99%
“…There is strong evidence demonstrating an association between cannabis and psychotic disorders, particularly frequent use of high tetrahydrocannabinol potency cannabis (Di Forti et al, 2019). Cannabis use has been estimated to be associated with approximately 12 and 15 excess life-years lost in women and men, respectively, in Danish register data (Weye et al, 2020). Earlier initiation of cannabis use and frequent cannabis use in adolescence are risk factors for later cannabis dependency (Leung, Chan, Hides, & Hall, 2020).…”
Section: Introductionmentioning
confidence: 99%